Sistem Informasi Rekam Medis Pada Puskesmas Tirtamulya Kabupaten Karawang - Surtika Ayumida; Ayumida, Surtika; Hakim, Lukmanul; Sabatini, Gabriela Juni (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
The development of information technology has grown so rapidly, one of which is a website-based information system which has many advantages over conventional paper-based systems and desktop-based information systems. This study aims to offer a solution to the Puskesmas Tirtamulya in Karawang Regency to implement a website-based medical record information system. The research method used is the application design with the Waterfall Model from Pressman. The results of the study created a website-based information system for the Puskesmas Tirtamulya, Karawang Regency with the following advantages: First, eliminating the possibility of duplicate patient data; Second, the process of searching for medical record data is easier to find; Third, it saves space because patient data and medical records are stored in the form of computer files, not in the form of paper documents; The four patient data and medical records are backed up online and periodically so that the data is stored safely; Fifth, the data stored in the system can be used as information as a basis for decision making by the puskesmas leadership. However, this website-based information system has requirements so that the system can run smoothly, namely further development costs are needed, competent management human resources are needed in the field of information technology, require data access subscription fees and require monthly system and network maintenance so that the system can go according to plan.